Effects of the Enhanced Recovery Program on the Recovery and Stress Response in Patients with Cancer Undergoing Pancreatoduodenectomy - Kapritsou, Maria; Papathanassoglou, Elizabeth; Konstantinou, Evangelos Ant; Korkolis, Dimitrios P.; Mpouzika, Meropi; Kaklamanos, Ioannis G.; Giannakopoulou, Margarita (My University, 2020)
Aim the study was the comparison of enhanced recovery after surgery (ERAS) versus conventional care (CON) protocols in patients undergoing pancreatoduodenectomy with regard to pain intensity, emotional response (optimism/sadness/stress), and stress biomarker levels (adrenocorticotropopic hormone, cortisol). We conducted a prospective two-group randomized controlled study with repeated measures in 85 patients with cancer pancreatoduodenectomy. In the ERAS group (N = 44), the ERAS protocol was followed, compared with the CON group (N = 41). We assessed pain with the numeric rating scale and a behavioral scale (Critical Care Pain Observation Tool), emotional responses (numeric rating scale), and serum adrenocorticotropopic hormone and cortisol levels at three time points: T1, admission day; T2, day of surgery; and T3, discharge day (ERAS) or the fifth day of stay (CON). Data were analyzed by linear mixed modeling to account for repeated measurements. We observed decreased postoperative pain in ERAS patients after adjusting for confounders (p =.002) and a trend for less complications. No significant associations with stress/emotional responses were noted. Only age, but not protocol, appeared to have a significant effect on adrenocorticotropopic hormone levels despite a significant interaction with time toward increased adrenocorticotropopic hormone levels in the ERAS group. In conclusion, despite its fast track nature, ERAS is not associated with increased stress in patients undergoing pancreatoduodenectomy and is associated with decreased pain.
Keywords: Pancreas fistula; Pancreaticojejunostomy; Stomach emptying